Anti-diabetic activity of Iphiona aucheri leaf extract (Bangladesh Journal of Pharmacology, 2020)
The methanolic extract of Iphiona aucheri leaves and its n-hexane, chloroform and aqueous fractions were screened for phytochemicals, cytotoxic effects, total phenolic contents, antioxidant and anti-diabetic properties. The methanolic extract was assessed for its in vivo anti-diabetic effects. The results indicated the presence of alkaloid, protein and amino acids, carbohydrates, glycosides, flavonoids, and saponins along with the highest brine shrimp lethality (90.7 ± 1.8%), α-amylase inhibition (60.2%) and free radical scavenging properties. The diabetic control indicated a significant (p